Պատմական բովանդակություն ունեցող հեղինակային նորակազմությունները Հայկ Խաչատրյանի պատմավեպերում - Սաղյան, Շ.
Нововедения (новообразования) в исторических романах Г. Хачатряна более 300. Одна часть из них имеет историческое содержание, которые соприкасаются к различным сторонам исторической жизни армянского народа: дворцовой, княжеской, воинской, житейской и т.д. Эти нововедения имеют 2 подвида: историзм-архаизм, текстовой (связочный). Все нововедения с историческим содержанием созданные Г. Хачатряном, являются разнородными, где преобладают структуры, составленные с двумя основными морфемами. There are more than 300 individual neologisms in the historic novels of Haik Khachatrian. Some of them are historically charged and 10 % o f them arc neologisms stipulated by the verbal context and 90 %-by the contexts interna atmosphere which touches divers aspects of historical life of Armenian pcoplc-court, princes, military, everyday life and etc. These individual neologisms are of 3 types: historical-aichaisms, textual (connective), mixed ones. All the individual historicaly charged neologisms employed by H. Khachatrian arc heterogeneous ones with the domination of two-morpheme structures.
Keywords: Բանասիրություն